Investigating the possibility of including key employees as assets in South African companies' financial statements - Kruger, Pieter (My University, 2019)
The purpose of this research study is to ascertain if a key employee in a company can be recorded as an asset on a company's balance sheet. Traditional accounting methods and record keeping does not allow for this in the corporate setting, as an employee does not comply with the traditional definition of an asset. The idea for this study came about when it was considered that football players are recorded as assets on the balance sheets of the football clubs that they play for. Certain criteria are used to determine their worth, based on their experience, past achievements and the skillset that they possess. The question was asked: Can corporate accounting be developed in such way as to recognise employees as assets to the company? The problem with this concept in the past has been that employees are classified as Human Capital, which is further classified as an intangible asset, without an objective monetary value. The other aspect that has hampered this process in the past has been the fact that employees are diverse, multi-dimensional, each with different levels of qualifications, experience and inert characteristics. The controllability of human beings and Human Capital as assets have also been difficult to overcome in the past. Football players also possess this diversity among them. Will it be possible to draw parallels between these two situations in order to facilitate this process? The design of this study includes an extensive literature review into the topic, as well as qualitative data collection, facilitated through in-person or telephonic interviews with corporate professionals. In this research study the importance of employees as Human Capital within an organisation has been found to be undeniable. Key employees exist in most, if not every organisation, big or small. They are the employees without whom a company 2 would not be where it is now. They possess a wide range of skills and attributes than contribute to the financial value of organisations. Up until now there has been great debate over the classification of employees as assets in organisations, but if one looks at the industry of football, they have been able to record their players as assets on their balance sheets. The possibility still exists for the formulation of a method in which traditional employees can be classified as assets, by drawing a parallel between the corporate environment and the football industry. Keywords: Asset, Balance Sheet, Football, Human Capital, Human Resource Accounting, Intellectual Capital, Intangible Asset, Key Employee.
MBA
Keywords: Human capital -- South Africa. Financial statements.